Prior treated tuberculosis and mortality risk in lung cancer - Liao, Kuang-Ming; Lee, Chung-Shu; Wu, Yu-Cih; Shu, Chin-Chung; Ho, Chung-Han (Frontiers in Medicine, 2023)
Background Lung cancer is one of the leading causes of cancer death worldwide, and tuberculosis (TB) is a common pre-existing disease. However, there is scarce literature studying the mortality risk in patients with prior TB and subsequent lung cancer. Methods We recruited lung cancer patients from the Taiwan Cancer Registry from 2011 to 2015 and classified them into two groups according to presence or absence of prior TB. We then matched them in a ratio of 1:4 using the exact matching approach. The mortality risk within 3 years after diagnosis of lung cancer was analyzed and compared between these two groups. Results During the study period, 43,472 patients with lung cancer were recruited, and of these, 1,211 (2.79%) patients had prior TB. After matching, this cohort included 5,935 patients with lung cancer in two groups: patients with prior TB before lung cancer (n = 1,187) and those without (n = 4,748). After controlling for demographic factors and comorbidities, the patients with prior TB had increased adjusted hazard ratios of 1.13 (95% CI: 1.04–1.23) and 1.11 (1.02–1.21) for all-cause and cancer-specific 3-year mortality, respectively, compared to the lung cancer patients without prior TB. Duration between TB and lung cancer (<1 year vs. 1–3 years vs. >3 years) had no differences for mortality risk. Conclusion In the present study, 2.79% patients with lung cancer had prior TB, which was associated with higher 3-year mortality after they developed lung cancer. The mortality risk with prior TB did not decrease even if >3 years passed before diagnosis of lung cancer.